2004
DOI: 10.1002/bjs.4547
|View full text |Cite
|
Sign up to set email alerts
|

Development of symptoms and complications in individuals with asymptomatic gallstones

Abstract: Nearly one in ten individuals with asymptomatic gallbladder stones in the general population may be expected to develop symptoms or complications that require treatment within 5 years. Age may be inversely related to the incidence of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
157
2
14

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 302 publications
(177 citation statements)
references
References 22 publications
4
157
2
14
Order By: Relevance
“…One was a 55 year old male Caucasian who had undergone routine USG as part of master health check up and the other was a 46 year old female .Studies have shown that incidental gallbladder carcinoma is found in about 0.5-1.1% of cholecystectomies for gall stone diseases 2,6 which was similar to our study [0.57%]. Gallbladder cancer is the most common cause of death from biliary malignancies.…”
Section: Discussionsupporting
confidence: 87%
“…One was a 55 year old male Caucasian who had undergone routine USG as part of master health check up and the other was a 46 year old female .Studies have shown that incidental gallbladder carcinoma is found in about 0.5-1.1% of cholecystectomies for gall stone diseases 2,6 which was similar to our study [0.57%]. Gallbladder cancer is the most common cause of death from biliary malignancies.…”
Section: Discussionsupporting
confidence: 87%
“…Similar findings have been reported more recently from Norway and Italy [10,11], and one could extrapolate that after 20 years, approximately two-thirds of individuals with AsGS would remain symptom free [6,7,9,[12][13][14] (Table 2). The data suggest that clinically silent GS in children and infants too are associated with low rates of complications and can be managed conservatively, unless complications occur.…”
Section: Natural Historysupporting
confidence: 86%
“…7,16,17 Although 73.8% of the cases in our study were aged 51 years and older, age did not influence mortality.…”
Section: Discussioncontrasting
confidence: 52%